2020
DOI: 10.1186/s12906-020-02935-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of acute radiation-induced Proctitis by Aloe vera: a prospective randomized, double-blind, placebo controlled clinical trial in Pelvic Cancer patients

Abstract: Background: Acute radiation-induced proctitis (ARP) is the most common side effect following radiotherapy for malignant pelvic disease. This study evaluated the efficacy of Aloe vera ointment in prevention of ARP. Methods: Forty-two patients receiving external-beam radiotherapy (RT) for pelvic malignancies were randomized to receive either Aloe vera 3% or placebo topical ointment during radiotherapy for 6 weeks. These patients were evaluated based on the severity (grade 0-4) of the following symptoms weekly: r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
0
7
0
1
Order By: Relevance
“…Aloe Vera has been used for centuries for its health, beauty, medicinal and skin care properties (Sahebnasagh et al, 2020). At present, a number of prescribed drugs come from plants.…”
Section: Aloe Vera Traditional Medicinal Uses In Various Ancient Culturesmentioning
confidence: 99%
See 3 more Smart Citations
“…Aloe Vera has been used for centuries for its health, beauty, medicinal and skin care properties (Sahebnasagh et al, 2020). At present, a number of prescribed drugs come from plants.…”
Section: Aloe Vera Traditional Medicinal Uses In Various Ancient Culturesmentioning
confidence: 99%
“…Although the mechanism of action by which Aloe Vera might facilitate healing is not clearly delineated, one hypothesis is that it exerts its effects as a result of antioxidant and immunomodulatory properties, and cyclooxygenase-2 suppression. One of active compounds in Aloe is salicylic acid, which can be converted into salicylate and thereby inhibits prostaglandin synthesis and the resulting inflammation (Sahebnasagh et al, 2020). Aloe Vera leaves contain anthraquinones, saccharides, vitamins, amino acids, minerals, enzymes, fatty acids, other emollient, healing, clotting, moisturizing, antiallergic, disinfectant, anti-inflammatory, astringent, choleretic, laxative, and other compounds.…”
Section: Various Utilizations and Compounds Of Aloe Veramentioning
confidence: 99%
See 2 more Smart Citations
“…). Sahebnasagh et al(86) demonstrated that Aloe vera topical ointment could be effective in prevention of RP; this finding is particularly notable given the non-existent toxicity profile of this product. In a randomized controlled phase II trial conducted by Saadipoor et al(87), oral nanocurcumin was not superior to placebo in preventing or mitigating symptoms of proctitis in patients undergoing RT for prostate cancer, but this fact could be due to the lack of a sufficiently large sample size to identify a statistically significant difference (underpowered study).…”
mentioning
confidence: 99%